TINJAUAN TEOLOGIS TERHADAP PELAYANAN PEREMPUAN DALAM LUKAS 81-3: THEOLOGICAL REVIEW OF WOMEN'S MINISTRY IN LUKE 81-3 - Rodenita Barus; Sri Astuti (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2021)
There are two views regarding the position of women in the church and society, namely the traditional notion that women are only housewives and career women, which means that women can take part in social and community functions. The purpose of writing this article is to expose the passage of Luke 8: 1-3 about the women who served the Lord Jesus and His entourage on the journey of preaching the gospel of the Kingdom of God. This paper uses a literature research and hermeneutical approach. Literally, the writer concludes that the phrase "women serving the group with their wealth" means adult women who are married or unmarried, helping and providing all the needs needed by the group, which has been confirmed by the Lord Jesus and His twelve disciples by property or money that comes from the woman herself. The service that this woman gave to the Lord Jesus and His twelve disciples was selfless service. Grammatically, the women who serve are adult women, either married or unmarried. The service that these women gave to the Lord Jesus and His twelve disciples was a service by donating the wealth and wealth owned by these women. The involvement of women in ministry is biblical.